Triggered Spark Gap Command Charger for High Repetition Rate Applications - Siew, Wee-Ong; Marimuthu, Jayaseelan; Chin, Oi-Hoong; Tou, Teck-Yong (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
A normal de resonant charger was transformed into a command-mode charger by connecting a spark gap at its output terminal, prior to the load circuit. This charging spark gap was triggered by a transformer connected in series, pulsed by a fast spark gap circuit. Noise suppression schemes were implemented throughout the command charger, in particular around the charging spark gap to order prevent misfiring. The ringing noise and spikes from the capacitor discharge and those of the stray capacitance of coaxial cable were strongly suppressed by a simple LCR circuit so that these would hot induce self-breakdown in the charging spark gap. This triggered spark gap command charger was tested to 2 kHz and < 10 kV with a resistive load. A transversely excited atmospheric CO2 laser was operated up to 300 Hz and (10-15) kV that was limited only by the flow rate of the laser gas mixture.